2021
DOI: 10.3390/ijms22094973
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Fungus Piriformospora indica Reprograms Banana to Cold Resistance

Abstract: Banana (Musa spp.), one of the most important fruits worldwide, is generally cold sensitive. In this study, by using the cold-sensitive banana variety Tianbaojiao (Musa acuminate) as the study material, we investigated the effects of Piriformospora indica on banana cold resistance. Seedlings with and without fungus colonization were subjected to 4 °C cold treatment. The changes in plant phenotypes, some physiological and biochemical parameters, chlorophyll fluorescence parameters, and the expression of eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 53 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…S. indica is an arbuscular mycorrhizal-like fungus that can colonize plant roots extensively and form a symbiotic relationship with its host. Accumulated evidence has shown that the colonization of S. indica could improve the nutrient absorption, promote plant growth and development, and enhance the resistance or tolerance of banana to abiotic and biotic stresses [5][6][7][8]. Bamboo fungus is a nutritious edible mushroom which not only has high medicinal value, but also has antioxidant and anti-microbial activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. indica is an arbuscular mycorrhizal-like fungus that can colonize plant roots extensively and form a symbiotic relationship with its host. Accumulated evidence has shown that the colonization of S. indica could improve the nutrient absorption, promote plant growth and development, and enhance the resistance or tolerance of banana to abiotic and biotic stresses [5][6][7][8]. Bamboo fungus is a nutritious edible mushroom which not only has high medicinal value, but also has antioxidant and anti-microbial activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the growth promoting effect, S. indica can also enhance the resistance of banana to both abiotic and biotic stresses. For example, Li et al reported that colonization of S. indica improved the banana cold resistance by stimulating antioxidant capacity, improving SS accumulation, and by regulating the expression of cold-responsive genes in banana leaves [6]; Bodjrenou et al found that colonization of S. indica improved the thermal resistance of banana [7]; Cheng et al reported that the fungus could improve the resistance of banana to Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) by regulating the antioxidant enzyme activities of banana root [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, beneficial microbes stimulate the formation of antioxidants in plants that efficiently neutralize ROS (Balestrini et al, 2018;Hamilton et al, 2012;Li et al, 2021;Noctor & Foyer, 1998). Antioxidants with major roles in plants include catalase, flavonoids, peroxidases, proline and superoxide dismutase (Noctor et al, 2018).…”
Section: Beneficial Microbes Harbour Mechanisms Of Protection Against...mentioning
confidence: 99%
“…The P. indica is well-known to be able to establish beneficial interactions with many different hosts, including monocotyledons such as barley, wheat, rice, corn, and dicotyledons, such as Arabidopsis and tobacco ( Qiang et al, 2012 ). The P. indica serves as an excellent model for beneficial microbes since it: (1) is genetically transformable and culturable in axenic conditions ( Zuccaro et al, 2009 ); (2) promotes plant growth and yield ( Kundu et al, 2021 ); (3) enhances plant tolerance against abiotic stress ( Li et al, 2021a ); and (4) primes plants for disease resistance against biotrophic and necrotrophic fungi ( Stein et al, 2008 ), oomycetes ( Trzewik et al, 2020 ), and viruses ( Fakhro et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%